Shear Response on GFRP RC Deep Beams with Horizontal and Vertical Web Reinforcement - Uppin, Prateek (2025)
A Master of Science thesis in Civil Engineering by Prateek Uppin entitled, “Shear Response on GFRP RC Deep Beams with Horizontal and Vertical Web Reinforcement”, submitted in November 2025. Thesis advisor is Dr. Farid Abed and thesis co-advisor is Dr. Tamer El-Maaddawy. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).